Personal Manuscripts: Copying, Drafting, Taking Notes - Durand-Guédy, Davic; Paul, Jürgen (Studies in Manuscript Cultures, 2023)
Some manuscripts have been produced for the personal use of their scribe only whereas a number of them are valued as autographs, most have been ephemeral and were discarded. This volume introduces a number of such manuscripts in a comparative perspective, from Japan to Europe through the Middle East. The main concern is the possibility of identifying the typical features of such manuscripts in terms of materials, visual organisation and content.